Moral foundations and criminality: comparing community members to prisoners and violent/non-violent offenders - Paruzel-Czachura, Mariola (Psychology, crime & law, 2025)
Morality is built upon individualizing (i.e. care, fairness) and binding (i.e. loyalty, authority, and purity) moral foundations, which are the systems that help people to make moral decisions and behave accordingly. Past research has found that moral foundations are related to past unethical behaviors, but we are the first to test them among people in prison. Specifically, we investigated individual differences in moral foundations in men and women in prison (N = 382) relative to Poles with no criminal record (N = 382), who were matched to the prisoner sample by sex and age. We showed that prisoners care about moral foundations, but just with a different intensity than people from the general population. We found that prisoners had lower individualizing moral foundations and higher binding moral foundations than participants from the general population. Violent prisoners had lower levels of care and purity than non-violent prisoners. Regarding sex differences, women scored higher in individualizing moral foundations than men, both among prisoners and non-prisoners. Lastly, women in prison scored higher in binding moral foundations than men in prison. Our study adds to the discussion of individual differences in moral foundations, which might help prevent crimes and enable the resocialization process.